Nanocrystalline cerium-doped Y-type barium hexaferrite; a useful catalyst for selective oxidation of styrene - Suthar, M.; Srivastava, A.K.; Joshi, R.K.; Roy, P.K. (Springer, 2020)
The cerium-doped Y-type barium hexaferrites Ba2−xCexCo2Fe12O22 (x = 0.0, 0.1, 0.2, and 0.3) were synthesized using the sol–gel auto combustion method. The synthesized nanocrystalline hexaferrite powders were characterized; especially it’s structural, morphological, and magnetic properties, through X-ray diffractometer, FTIR spectroscopy, scanning electron microscopy and vibrating sample magnetometer, respectively. The effects of catalyst amount, reaction temperature and time, solvent and oxidizing agent required for the entire conversion of styrene to benzaldehyde were also examined with pure Y-type barium hexaferrite (BrM). The catalytic performance of the BrM powder was measured for its suitability in the oxidation of styrene using various oxidants, and the isolated yield of the benzaldehyde was calculated using the column chromatography separation. The as-prepared 20 mg BrM samples showed total conversion of styrene and 66% isolated yield for benzaldehyde at 120 °C for 24 h in the presence of trifluoroacetic acid as an oxidant. The effect of cerium doping on the benzaldehyde selectivity was also analyzed at optimized conditions and found that cerium-doped samples showed excellent catalytic performance. Paralleled with the pristine barium hexaferrite, the catalytic efficiency was significantly enriched and exhibited its maximum performance with Ba1.8Ce0.2Co2Fe12O22 ferrite, almost 71% selectivity was achieved with the same reaction conditions. This enhanced performance was correlated with the XPS studies for x = 0.2 sample. The as-prepared catalyst was magnetically separable to reprocess. There was no remarkable loss of catalytic activity when it was reprocessed for five consecutive trials. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.